2020
DOI: 10.7150/jca.45822
|View full text |Cite
|
Sign up to set email alerts
|

MST4 inhibits human hepatocellular carcinoma cell proliferation and induces cell cycle arrest via suppression of PI3K/AKT pathway

Abstract: Objective: MST4 has exhibited functions in regulating cell polarity, Golgi apparatus, cell migration, and cancer. Mechanistically, it affects the activity of p-ERK, Hippo-YAP pathway and autophagy. The aim of this study is to further examine the functions of MST4 in hepatocellular carcinoma (HCC) and the underlying mechanism. Methods: The expression level of MST4 in HCC and noncancer adjacent liver tissues was determined by qRT-PCR and immunohistochemistry staining. Wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Next, we investigated the mechanism by which MST4 suppressed the EMT phenotype and the invasive and metastatic potential of HCC cells. In our previous study, we have unraveled an inhibitory effect of MST4 on PI3K/AKT pathway 29 . Here, we investigated whether the inactivation of PI3K/AKT pathway is essential for the suppressed EMT phenotype by MST4 high expression in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we investigated the mechanism by which MST4 suppressed the EMT phenotype and the invasive and metastatic potential of HCC cells. In our previous study, we have unraveled an inhibitory effect of MST4 on PI3K/AKT pathway 29 . Here, we investigated whether the inactivation of PI3K/AKT pathway is essential for the suppressed EMT phenotype by MST4 high expression in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Another finding reported that PI3K/AKT can sustain NF-kB activation in the absence of TGF-β1, thus inducing EMT and promoting tumor formation and metastasis 60 . Our previous study illustrated that MST4 inhibits HCC cell proliferation by inactivating the PI3K/AKT signaling pathway 29 . Here, our data further confirmed that the PI3K inhibitor can reverse the EMT phenotypic change and the increased capabilities of migration and invasion of HCC cells caused by the MST4 functionally inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The core components of the Hippo signaling pathway are verified as a kinase cascade, which act directly on the primary downstream effectors, the yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) by phosphorylation, and thereby suppressing transcription process of downstream targeted genes ( 13 ). Recently, it has been proved that the dysregulation of the Hippo signaling pathway lead to tumorigenesis, development and metastasis of diverse tumors, including lung adenocarcinoma ( 14 ), breast cancer ( 15 ), hepatocellular carcinoma ( 16 ), gastric cancer ( 17 ) and so on. However, fewer studies focus on the effects of the Hippo signaling pathway on LUSC.…”
Section: Introductionmentioning
confidence: 99%